Erratum to: Localization and resummation of unstable instantons in 2d Yang-Mills - Luca Griguolo; Rodolfo Panerai; Jacopo Papalini; Domenico Seminara; Itamar Yaakov (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP06(2024)188